HEARTS in the Americas clinical pathway. Strengthening the decision support system to improve hypertension and cardiovascular disease risk management in primary care settings - Rosende, Andres; DiPette, Donald J.; Martinez, Ramon; Brettler, Jeffrey W.; Rodriguez, Gonzalo; Zuniga, Eric; Ordunez, Pedro (Frontiers in Cardiovascular Medicine, 2023)
HEARTS in the Americas, the regional adaptation of the WHO Global HEARTS Initiative, is being implemented in 24 countries and over 2000 primary healthcare facilities across the region. One of its systematic interventions is implementing a standardized, simple, and directive hypertension treatment protocol in the primary health care setting. The treatment protocol is a key driver for hypertension control and a recommendation of the 2021 WHO hypertension guideline. This paper describes the results of a multicomponent, stepwise, quality improvement intervention designed by the HEARTS in the Americas to support advances in hypertension treatment protocols and evolution towards the Clinical Pathway in 16 HEARTS-implementing countries. While preserving the hypertension treatment protocol as the core, HEARTS clinical pathway integrates other relevant components to improve cardiovascular disease risk management. This study confirms that this intervention was feasible, acceptable, and instrumental in achieving progress in all countries and all three domains of improvement: implementation, blood pressure treatment, and cardiovascular risk management. Adopting and implementing the HEARTS Clinical Pathway can improve the efficiency and effectiveness of hypertension and CVD programs.